A reduced order model for FSI of tank walls subject to wave impacts during sloshing - Bos, R.W.; van der Eijk, M.; den Besten, J.H.; Wellens, P.R. (International shipbuilding progress, 2022)
Loads due to wave impacts are a limiting factor in the design of liquefied natural gas (LNG) tankers and their insulation. The current methodology considers the load independent from the response of the tank. Better tanks can be designed by knowing the effect of the interaction between the wave loads and the response, however predicting these effects is computationally expensive. In this paper a new application of the non-hydrostatic shallow water equations are presented, namely as a reduced order model (ROM) for fluid structure interaction for wave impacts. Our ROM is compared to a high fidelity model. The proposed ROM is fast and accurately predicts the total impulse and added mass, and therefore the general behaviour of the structure during the free vibration phase. It does however not always accurately predict the maximum force. It is therefore considered an appropriate tool for a first screening of the loads for which fluid-structure interaction is important, after which a more accurate method can be used to evaluate the most interesting cases. A sensitivity study is performed for various impact angles and velocities, showing that the importance of fluid structure interaction depends highly on the specific situation.